THE ESSENTIAL OF CAPACITY DEVELOPMENT IN THE POST CONFLICT COUNTRIES - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Capacity development is a concept which is broader than organizational development in that it includes an emphasis on the overall system, environment or context within which individuals, organizations and societies operate and interact (and not simply a single organization)(UNDP, 1998). It can also be the process of developing competencies and capabilities in individuals, groups, organizations, sectors or countries which will lead to sustained and self-generating performance improvement (Aus AID, 2004). Capacity building is badly needed in South Sudan. Much of the adult population spent its youth in war with a minority having access to education abroad; therefore, everything from education, technical training, business training, entrepreneurship and other capacity is required. Anyone doing business in South Sudan should definitely consider a strong CSR element in capacity building, which could take various forms: vocational training, mentoring, or supplementary training. Note that due to the length of the war, there is a general absence of skilled labor or a work ethic in South Sudan. Startup companies may need to consider importing some skilled labor, or trying to identify individuals returning from various Diaspora with the requisite skills (USAID, 2012). Capacity development has the following attributes; Knowledge, Skills, Competencies, Capabilities and innovations